Adherence to individualized recall intervals for oral health examinations - Anna Haukka; Minna Kaila; Jari Haukka; Anna M. Heikkinen (Wiley, 2023)
Abstract Objectives The aim of this follow‐up study was to investigate whether adults attend an oral health examination (OHE) based on their individual recall interval (IRI) without a reminder recall system. Methods The study population included adults who were attending an OHE recommended by their dentists based on their IRI in public oral healthcare clinics of Helsinki City January 1, 2009−December 31, 2009. The inclusion criteria were as follows: alive until the end of IRI, length of the IRI of 12-60 months, and study participants had not been treated successfully by a dental specialist during the IRI period (n = 41,255). We used a multinomial model to identify the factors associated with the timing of OHE. The following predictors were included: oral health indices such as Decayed Teeth and the Community Periodontal Index, the length of the IRI based on an OHE in 2009, age, gender, socioeconomic status, presence of chronic diseases, and emergency appointment. Results were presented as odds ratios with 95% confidence intervals. Results The OHE based on IRI occurred for 7505 individuals (18.2%) and the OHE was late for 9159 individuals (22.2%). A total of 24,591 (59.6%) adults did not undergo follow‐up OHE based on the IRI period of on time or late. Those who came on time for follow‐up OHE experienced less caries than those who came later. There was not much difference in periodontal health between the groups. The models indicated that having an emergency appointment was associated with a higher probability of having an OHE. A long IRI (37-60 months) was associated with a higher probability of not participating in OHE even late. Conclusions It would be beneficial for patients to take appointments based on the recall interval. The results of this study indicated that more needs to be done to increase awareness in the adult population of the benefits and availability of follow‐up OHEs based on their IRI in oral healthcare.